2011
DOI: 10.1074/jbc.m111.260992
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Streptococcal Adhesin P (SadP) Protein Recognizing Galactosyl-α1–4-galactose-containing Glycoconjugates

Abstract: Background: Adhesion is a prerequisite to infectious diseases. Results: A novel streptococcal Gal␣1-4Gal-recognizing adhesin was identified, which has no homology to known Gal␣1-4Gal-recognizing proteins. Conclusion: SadP is an example of convergent evolution of adhesins to binding to the same receptor, Gal␣1-4Gal, abundant in glycolipids. Significance: Identification of SadP helps to understand the molecular basis of streptococcal pathogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 70 publications
3
52
1
Order By: Relevance
“…We demonstrated that SadP1 contributes to the adhesion to human IEC by binding of Gb3/CD77 confirming previous functional studies on recombinant galabiose-binding N-terminal domain of SadP recognizing Gb3/CD77 as its natural glycolipid host-cell receptor [11, 47]. Recent studies on the structure of SadP1 in interaction with Gb2, which is analogous to Gb3/CD77, identified 10 AA critical for binding of SadP1 to the homologous structure of galabiose of Gb2 [47].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We demonstrated that SadP1 contributes to the adhesion to human IEC by binding of Gb3/CD77 confirming previous functional studies on recombinant galabiose-binding N-terminal domain of SadP recognizing Gb3/CD77 as its natural glycolipid host-cell receptor [11, 47]. Recent studies on the structure of SadP1 in interaction with Gb2, which is analogous to Gb3/CD77, identified 10 AA critical for binding of SadP1 to the homologous structure of galabiose of Gb2 [47].…”
Section: Discussionsupporting
confidence: 88%
“…Analysis of SadP binding specificity to galabiose present in the Gbs receptors revealed the highest specificity to the globotriaosylceramide Gb3/CD77 receptor [11]. Gb3/CD77 receptors are abundant in various host tissues including human and pig small intestine in the precursor (Gb3/CD77) or mature form (globotetraosylceramide Gb4) [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Suilysin, the extracellular protein factor, along with a muramidase-released protein have also been shown to be linked to, but not essential for, the full virulence of S. suis [21]. GapdH [22], Enolase [23], [24], Fibronectin/Fibrinogen-binding protein [25], HAM1 [26] and Adhesion [27], [28], [29], [30], [31], [32] have been shown to be involved in S. suis adherence and virulence. Serum opacity-like factor [33], D-Alanylation of Lipoteichoic Acid [34], Peptidoglycan GlcNAc deacetylase [35], IgA protease [36], [37], TroA [38], SodA [39], SsFHB [40] and Subtilisin-like serine protease [41], [42], [43] are also considered to be related to S. suis virulence.…”
Section: Introductionmentioning
confidence: 99%
“…The isolates differed by an inserted region, with genes which were likely inserted as a whole, but the origin of this inserted sequence is not well understood. The isolates also had different SadP genes, previously characterized as an adhesin as well as a factor H binding protein which may contribute to zoonotic potential (Ferrando et al, ) and is considered a putative virulence factor of S. suis (Kouki et al, ; Pian et al, ).…”
Section: Discussionmentioning
confidence: 99%